2020
DOI: 10.1037/prj0000372
|View full text |Cite
|
Sign up to set email alerts
|

Individual placement and support in the Netherlands: Past, present, and future directions.

Abstract: Objective: This article addresses the rise of individual placement and support (IPS) within vocational services for people with severe mental illness (SMI), the current state of affairs, and future directions of IPS in the Netherlands. Method: Review of the literature on IPS in the Netherlands, analysis of registration data, and exploration of future avenues for IPS in Dutch mental health care. Findings: In the first decade of this century, an implementation study showed that IPS was feasible in the Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The success of the IPS Learning Community has been an inspiration to IPS advocates outside the USA, modelling effective IPS implementation strategies and the power of peer learning. Furthermore, IPS Employment Center colleagues have fostered international growth by providing encouragement, mentoring and consultation (van Weeghel et al ., 2020).…”
Section: Enablers Of International Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of the IPS Learning Community has been an inspiration to IPS advocates outside the USA, modelling effective IPS implementation strategies and the power of peer learning. Furthermore, IPS Employment Center colleagues have fostered international growth by providing encouragement, mentoring and consultation (van Weeghel et al ., 2020).…”
Section: Enablers Of International Expansionmentioning
confidence: 99%
“…In England, the National Health Service committed to ‘doubling access to IPS services by 2021’ (Melleney and Kendall, 2020). In the Netherlands, a broad group of mental health providers, vocational rehabilitation and welfare stakeholders, along with service users and their families, adopted a national action plan for the recovery of people with serious mental illness, emphasising that IPS should be accessible to the entire target population (van Weeghel et al ., 2020).…”
Section: Enablers Of International Expansionmentioning
confidence: 99%
“…However, due to its broad perspective, BPR is not designed to help people to attain goals such as paid employment, which would then require specific expertise it could not support. More specialized methods may be needed for specific goal areas, such as IPS ( 42 ), which is specifically designed to help individuals gain and maintain paid employment and is widely available in the Netherlands ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various interventions and rehabilitation approaches designed for people with complex and persistent mental health needs have been described in the literature. Examples are cognitive adaptation training [CAT; (28,29)], individual placement and support [IPS; (30)], the Boston University approach to Psychiatric Rehabilitation (31), and wellness recovery action plan [WRAP; (32)]. In addition, research showed that focus on an expected maximum length of stay encourages people in their recovery and supports long-stay service users to move to a more independent setting (33).…”
Section: Introductionmentioning
confidence: 99%